CGIAR initiative on One Health: Protecting human health through a One Health approach - Hung Nguyen-Viet; Hoffmann, Vivian; Bett, Bernard K.; Fèvre, Eric M.; Moodley, Arshnee; Mateo-Sagasta, Javier; Mohan, Chadag V.; Daszak, P.; Bonfoh, B. (International Livestock Research Institute, 2022)
This initiative aims to show how a One Health approach – which recognizes the interconnections between people, animals, plants, and their shared environment – can help reduce antimicrobial resistance, improve food and water safety, and manage zoonotic diseases, leading to better human, animal, and environment health. It forms part of CGIAR’s new research portfolio, delivering science and innovation to transform food, land, and water systems in a climate crisis.